“English Polite Utterances” Terhadap Siswa/i Kelas XII SMA Nurul Hasanah Medan - Zuindra Zuindra; Bima Prana Chitra; Misla Geubrina (Forum Kerjasama Pendidikan Tinggi, 2020)
In everyday life, a system that regulates how humans should get along is needed. The system of rules in this association is mutual respect which is usually called courtesy. Manners are very necessary, especially in communication. Politeness in communication must be instilled and developed in each individual. However, nowadays politeness speech has seemed to fade, especially among students. So, it is hoped that through the